Mainstreaming Disabilities in the Education Sector: Implementation of Inclusive Elementary School Policy in Malang City - iswanto, denny (PANGRIPTA, 2025)
Inclusive education ensures equal access to education for persons with disabilities. This study examines the implementation of inclusive basic education policies in Malang City and the challenges in mainstreaming disability rights. Despite the government's commitment through Law No. 8/2016 and PP No. 13/2020, disparities persist. Of 285 primary schools, only 95 offer inclusive education, with many lacking disability-friendly facilities. Using a descriptive qualitative approach and secondary data analysis, findings reveal key challenges: limited trained teachers, inadequate support staff, and insufficient infrastructure. The study highlights the need for enhanced teacher training, expanded inclusive schools, and improved facilities to ensure equitable education access.